2023
DOI: 10.3390/biomedicines11030865
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro Evaluation of the Most Active Probiotic Strains Able to Improve the Intestinal Barrier Functions and to Prevent Inflammatory Diseases of the Gastrointestinal System

Abstract: Background: The integrity of the intestinal barrier is fundamental to gut health and homeostasis; its damage can increase intestinal permeability, with translocation of bacteria and/or endotoxins from gut, and the onset of various intestinal diseases. Lactobacillus spp. is one of the most common probiotics normally found in fermented foods and dairy products and is known for its anti-inflammatory and immunomodulatory properties and for its ability to protect and enhance the intestinal barrier functions. The ai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 54 publications
0
9
0
Order By: Relevance
“…In addition to the decrease of relative abundance of Proteobacteria, Bacteroidetes, and Actinobacteria in the intestinal tract of mice with diarrhea caused by ginseng polysaccharide, long‐term administration of ginseng extract can also significantly reduce the abundance of Bacteroidetes in rats 35 . Lactobacillus is the normal bacteria in the intestinal tract, which can reduce the attachment of pathogenic bacteria in the intestinal tract and enhance the immune function of the body by enhancing the intestinal barrier function 36–38 . Studies have shown that Akkermansia can maintain the integrity of intestinal mucosa and also help improve the body's immunity 39,40 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to the decrease of relative abundance of Proteobacteria, Bacteroidetes, and Actinobacteria in the intestinal tract of mice with diarrhea caused by ginseng polysaccharide, long‐term administration of ginseng extract can also significantly reduce the abundance of Bacteroidetes in rats 35 . Lactobacillus is the normal bacteria in the intestinal tract, which can reduce the attachment of pathogenic bacteria in the intestinal tract and enhance the immune function of the body by enhancing the intestinal barrier function 36–38 . Studies have shown that Akkermansia can maintain the integrity of intestinal mucosa and also help improve the body's immunity 39,40 .…”
Section: Discussionmentioning
confidence: 99%
“…35 Lactobacillus is the normal bacteria in the intestinal tract, which can reduce the attachment of pathogenic bacteria in the intestinal tract and enhance the immune function of the body by enhancing the intestinal barrier function. [36][37][38] Studies have shown that Akkermansia can maintain the integrity of intestinal mucosa and also help improve the body's immunity. 39,40 This is consistent with our findings.…”
Section: Discussionmentioning
confidence: 99%
“…As a result, the use of alternative therapies based on probiotics, in particular lactobacilli, is developing more and more both in the medical field and in agriculture [ 20 , 47 , 48 ]. The intake of probiotics is understood as the application of live microorganisms in order to obtain a health benefit, both in the prevention of various diseases and in the improvement of the general conditions of the host organism [ 24 , 25 , 26 , 27 , 28 , 29 , 49 ].…”
Section: Discussionmentioning
confidence: 99%
“…Probiotics may act as preventing agents against several bacterial pathogens by limiting binding locations on mucosal epithelial cells and regulating the host immunological response, therefore enhancing the gut barrier [ 4 ]. The diverse strengths of probiotics are also associated with the control of the intestinal microbiome, justification of dietary intolerances (like lactose intolerance), bioavailability enhancement of macro- and micro-nutrients, and weakening of allergic symptomatology in vulnerable persons [ 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…The diverse strengths of probiotics are also associated with the control of the intestinal microbiome, justification of dietary intolerances (like lactose intolerance), bioavailability enhancement of macro- and micro-nutrients, and weakening of allergic symptomatology in vulnerable persons [ 5 ]. These beneficial impacts of probiotics are mainly associated with the prevention of several disorders by decreasing symptom severity [ 1 , 2 , 3 , 4 , 5 ]. There is currently substantial evidence that probiotic supplementation could act as a protective agent against allergic symptoms, tumor malignancies, neurodegenerative and psychiatric diseases, cardiovascular diseases, obesity, diabetes, lactose intolerance, inflammatory bowel disease, immune system disorders, non-alcoholic fatty liver disease, diarrhea, irritable bowel syndrome, etc.…”
Section: Introductionmentioning
confidence: 99%